Parallel interleukin 5 synthesis by eosinophils in duodenal and skin lesions of a patient with dermatitis herpetiformis. Issue 1 (July 1995) - Desreumaux, P; Janin, A; Delaporte, E; Dubucquoi, S; Piette, F; Cortot, A; Capron, M; Colombel, J F
Abstract : A 59 year old man is presented with a diagnosis of dermatitis herpetiformis. Duodenal and skin biopsy specimens from blisters of both recent and late onset were collected before treatment. Electron microscopy, immunohistochemistry, and in situ hybridisation were performed to analyse the presence of activated eosinophils and the local synthesis of interleukin 5 (IL5). Parallel state of eosinophil activation and IL5 synthesis was found in the duodenal mucosa with total flat mucosa and in skin vesicles of recent onset. It is suggested that duodenal and cutaneous eosinophils can synthesise IL5 and then participate in small bowel and skin lesions.